How to define end-diastole and end-systole?: Impact of timing on strain measurements - Mada, Razvan O; Lysyansky, Peter; Daraban, Ana M; Duchenne, Jürgen; Voigt, Jens-Uwe (JACC. Cardiovascular imaging, 2015)
This study aimed to investigate to what extent timing definitions influence strain measurements and which surrogates are reliable and feasible to define end-diastole (ED) and end-systole (ES) during speckle-tracking (STI) analysis. Current STI-based strain measurements are highly automated. It remains unclear when a particular analysis software defines the zero baseline and the systolic strain measurement position. A total of 60 subjects (20 healthy volunteers, 20 patients with coronary artery disease, and 20 patients with typical left bundle-branch block) underwent a complete echocardiographic examination. In one-half of them, a real M-mode through the mitral valve was acquired for each electrocardiographic (ECG) lead of the echo machine. Timing of peak R and automatic ECG trigger were compared with mitral valve closure for every electrode. Mitral and aortic valve closure, as observed in the apical 3-chamber view, served as reference for ED and ES. With the use of these references, end-systolic global longitudinal strain (ES-GLS) and end-systolic segmental longitudinal strain (ES-SLS) longitudinal end-systolic strain were measured at baseline and after changing the definition of either ED or ES by ±4 frames. Furthermore, strain and volume curves derived from the same tracking, as well as the Doppler interrogation of the valves, were compared with the references. Depending on the selected lead, timing of the ECG-derived time markers changed considerably compared with mitral valve closure. Changing the definition of ED and ES resulted in significantly different ES-GLS and ES-SLS values in all subjects. ES-SLS in dyssynchronous hearts showed the highest sensitivity to timing definition. From all methods, spectral Doppler was the most reliable time marker in all subjects (p > 0.05). Exact temporal definition of ED and ES has a major impact on the accuracy of strain measurements. After direct observation of the valves, Doppler evaluation is the best means for characterizing ED and ES for STI analysis.